Factors controlling SOC stability in colluvial soils under contrasting climate and soil weathering conditions. (24th October 2022) - Zhao, Pengzhi; Doetterl, Sebastian; Wang, Zhengang; Hoyt, Alison M.; Wang, Enheng; Yu, Hanqing; Quijano, Laura; Fallu, Daniel J.; Brown, Antony G.; Six, Johan; Van Oost, Kristof
Abstract: Although agricultural colluvial soils are important storage for soil organic carbon (SOC), the mechanisms underlying colluvial (cumulative soils) SOC stability have received little attention so far. In this study, we aim to understand to what extent the main controls on colluvial SOC stability differ from those observed in non‐colluvial soils. Paired soil profiles (non‐colluvial versus colluvial) were collected from five sites which differ in climate, soil geochemical background and cultivation history. Topsoil (0–10 cm) and subsoil (30–50 cm) were analysed for SOC fractions, mineral composition, potential soil respiration and radiocarbon content. Our analysis showed that for non‐colluvial soils, climate, cultivation history and weathering degree have significant effects on potential soil respiration. In contrast, for colluvial soils, the most influential factor for potential soil respiration was the rate of accretion and this was independent of climatic and geochemical context. Furthermore, accretion rates indirectly affected potential soil respiration by interacting with the degree of weathering of deposited soil. This changed the mineral matrix of colluvial soil settings and thereby may enhance soil mineral‐related SOC stabilisation mechanisms. Together, these results suggest that the dominant controls on SOC stability in colluvial soils differ from those in non‐colluvial soils, and the soil accretion rate is the most important control on colluvial SOC stability in agricultural systems. Highlights: The dominant controls on SOC stability in colluvial and non‐colluvial soils were compared. Climate and mineral weathering predominantly control SOC stability in non‐colluvial soils. In contrast, the accretion rate is the key factor controlling colluvial SOC stability. Accretion rate drives the role of mineral weathering in colluvial SOC stability.